2014
DOI: 10.3402/meo.v19.22522
|View full text |Cite
|
Sign up to set email alerts
|

Teaching patient-centered communication skills: a telephone follow-up curriculum for medical students

Abstract: BackgroundTo encourage medical students’ use of patient-centered skills in core clerkships, we implemented and evaluated a Telephone Follow-up Curriculum focusing on three communication behaviors: tailoring education to patients’ level of understanding, promoting adherence by anticipating obstacles, and ensuring comprehension by having patients repeat the plans.MethodsThe intervention group consisted of two different cohorts of third-year medical students in longitudinal clerkships (n=41); traditional clerkshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 16 publications
1
34
0
5
Order By: Relevance
“…Educational content assessed included 'ask-teach-ask' skills such as asking the patient about their concerns, mapping out self-management action plans and 'closing the loop' by asking the patient to repeat the content back in their own words. The results demonstrated that the intervention group obtained significantly higher performance scores for three of the seven educational tasks which specifically related to seeking patient concerns, providing information and checking patient understanding (Saba et al, 2014).…”
Section: Patient Education Training For Health Professional Studentsmentioning
confidence: 79%
See 4 more Smart Citations
“…Educational content assessed included 'ask-teach-ask' skills such as asking the patient about their concerns, mapping out self-management action plans and 'closing the loop' by asking the patient to repeat the content back in their own words. The results demonstrated that the intervention group obtained significantly higher performance scores for three of the seven educational tasks which specifically related to seeking patient concerns, providing information and checking patient understanding (Saba et al, 2014).…”
Section: Patient Education Training For Health Professional Studentsmentioning
confidence: 79%
“…Less than half of all studies within the review specifically assessed student performance following the intervention (Campbell et al, 1996;Papadakis et al, 1997;Bosse et al, 2012;Saba et al, 2014). In addition, only four studies assessed student self-efficacy in relation to patient education (James et al, 2003;Goldenberg et al, 2005;Bosse et al, 2012).…”
Section: Patient Education Training For Health Professional Studentsmentioning
confidence: 99%
See 3 more Smart Citations